Estrangement of Meaning in a Wealth of Information - Fabian Muniesa (Sociologica)
The expression offered by the editors as a prompt for thought (“observing technologies of observation”) is twisted here, briefly and provocatively, in a kind of radical way, intensifying both its informational (cybernetic) connotation and the intuition of a spiraling (psychotic) twirl. Reminiscences of “Von Foerster’s conjecture” (a theory of alienation in second-order observation once formulated by Jean-Pierre Dupuy) are used in order to interrogate the depletion of signification in a society that is now conceived of as a computational product. The problem of aesthetics, the essay concludes, becomes then crucial.